Cytoplasm-Translocated Ku70/80 Complex Sensing of HBV DNA Induces Hepatitis-Associated Chemokine Secretion - Li, Young; Wu, Yang; Zheng, Xiaohu; Cong, Jingjing; Liu, Yanyan; Li, Jiabin; Sun, Rui; Tian, Zhigang G.; Wei, Haiming M. (Frontiers in Immunology, 2016)
Chronic hepatitis B remains a serious disease, mainly owing to the severe pathological consequences of persistent hepatitis B virus (HBV) infection of carriers, which is difficult to cure using current therapies. When the immune system responds to hepatocytes experiencing rapid HBV replication, effector cells (such as HBV-specific CD8+ T cells, NK cells, NKT cells and other subtypes of immune cells) infiltrate the liver and cause hepatitis. However, precisely how these cells are recruited remains unclear. In the present study, we found that the cytoplasm-translocated Ku70/80 complex in liver-derived cells sensed cytosolic HBV DNA and promoted hepatitis-associated chemokine secretion. Upon sensing HBV DNA, DNA-dependent protein kinase catalytic subunit (DNA-PKcs) and PARP1 were assembled. Then IRF1 was activated and translocated into the nucleus, which upregulated CCL3 and CCL5 expression. Because CCR5, a major chemokine receptor for CCL3 and CCL5, is known to be critical in hepatitis B, Ku70/80 sensing of HBV DNA likely plays a critical role in immune cell recruitment in response to HBV infection.